HUBUNGAN PERGAULAN TEMAN SEBAYA DENGAN HASIL BELAJAR PESERTA DIDIK SD INPRES TARUS 1 - Treesly Y. N. Adoe; Marianus Genaro Pani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the relationship between peer interactions and the learning outcomes of students at SD Inpres Tarus 1. This research uses quantitative methods with an associative approach. The data analysis used is inferential statistical analysis. The population in this study were students at SD Inpres Tarus 1 in grades II to VI totaling 425 people. Sampling used the Slovin formula with an error rate of 10%, resulting in a sample of 81 people. The sampling technique used simple random sampling. The instrument validity test used the Pearson correlation test, the instrument reliability test used the Alpha Cronbach test. Simple regression analysis techniques were used to determine the coefficient of determination between each variable. Hypothesis testing used the Pearson correlation test. The results showed that there was a relationship between peer relationships and learning outcomes. Peer relationships contributed 6.6% to the learning outcomes of students at SD Inpres Tarus 1.